Ozone Loss Inside the Northern Polar Vortex During the 1991-1992 Winter - Proffitt, M. H.; Aikin, K.; Margitan, J. J.; Loewenstein, M.; Podolske, J. R.; Weaver, A.; Chan, K. R.; Fast, H.; Elkins, J. W. (2004)
Measurement made in the outer ring of the northern polar vortex from October 1991 through March 1992 reveal an altitude dependent change in ozone, with decrease at the bottom of the vortex and substantial increase at the highest altitudes accessible.